Prevention of Smoking among High School Students in the Situation of the Coronavirus Disease 2019 Epidemic, Nakhon Ratchasima Province - จึงสมเจตไพศาล, ภัทรพล; ทวยมีฤทธิ์, สันติ (Journal of Health Science of Thailand, 2022)
The purpose of this action research was to study the smoking situation of high school students and to develop smoking prevention program in high school student as well as to evaluate the program in the situation of the 2019 coronavirus disease epidemic in Nakhon Ratchasima Province, The samples were divided into 4 groups as follows: (1) 394 high school students, (2) 18 teachers, (3) 24 parents of students, and (4) 18 public health officers. Research tools included document analysis, questionnaires, group discussions, and in-depth interviews. Qualitative data were evaluated by categorization and grouping, whereas quantitative data were studied by descriptive statistics, including frequency, percentage, mean, and standard deviation. It was found that: (1) all 6 schools had clearly defined smoking prevention policies; the activities often differed depending on the context of each school. High school students had a very high level of knowledge about tobacco toxicity (Mean=4.00; SD=0.55); and the overall attitude of the students towards smoking was at high level (Mean=3.94; SD=0.53). (2) Preventing smoking among high school students should include online activities to educate about smoking prevention. They should have activities such as cover-dance contests, sports competitions, short film contests, non-smoking campaigns, etc. In addition, there should be intensive selection of student recruitment and adjustment of the environment to be clean, beautiful, and clear. (3) Evaluation of the operation under the SKIN Plus model could be used in practice as appropriate, and could be applied in any location with the context close to Nakhon Ratchasima Province. The suggestion is that schools should find measures to control the sale of cigarettes to students around the school areas and should allow students to participate in the design of ongoing campaign activities.